The Relationship between the Implementation of the Hospital Management Information System (SIMRS) and the Quality of Administrative Services at the Outpatient Clinic of Idaman Hospital, Banjarbaru - Taziah Aulia Rizki; Raziansyah; Annalia Wardhani (International Journal of Science and Environment (IJSE), 2026)
The Taziah Aulia Rizki. NIM 20221326122021 Hospital Administration Study Program. “The Relationship Workload and Doctors' Attitudes with the Completeness of Informed Consent Forms at RSD Idaman Banjarbaru City”. Adviser: H. Raziansyah, S.Kp., MPH and Annalia Wardhani, S.Kep, Ns, M.Kep. The World Health Organization (WHO) states that an integrated health information system is capable of accelerating administrative processes, reducing data errors, and improving coordination among service units (WHO, 2022). This study aimed to determine the relationship between the implementation of the Hospital Management Information System (HMIS) and service quality at the Outpatient Department of RSD Idaman Banjarbaru. This study used a quantitative method with a cross-sectional approach. The study population consisted of 102 administrative staff and 4,092 outpatients in January. The sample comprised 51 administrative staff and 51 outpatients selected using a nonprobability sampling technique. Data were collected using questionnaires and then analyzed using the Spearman Rank test with the assistance of SPSS version 25. The results showed that most respondents assessed the implementation of HMIS as being in the good category; 71.0% assessed the quality of administrative services as being in the good category, while 29.0% assessed it as being in the poor category. The analysis results indicated a significant relationship between the Hospital Management Information System (HMIS) and the quality of administrative services (p-value = 0.000; r = 0.568). The conclusion of this study is that there is a significant relationship between the Hospital Management Information System (HMIS) and the quality of administrative services at the Outpatient Department of RSD Idaman Banjarbaru in 2026.